ENHANCING LEARNING THROUGH THE VISUAL ARTS: EXPLORING EFFECTIVE TEACHING METHODS - Giyosiddinova Makhmudakhan Alisherovna (Galaxy International Interdisciplinary Research Journal, 2024)
Visual arts education plays an important role in students’ creativity, critical thinking, and self-expression. This research paper explores teaching methodologies that help optimize the learning experience in visual arts classrooms. By exploring different approaches, techniques, and best practices, teachers can enhance student engagement, skill development, and artistic appreciation in the visual arts.